Bendable n‐Type Metallic Nanocomposites with Large Thermoelectric Power Factor. Issue 4 (11th November 2016) - Chen, Yani; He, Minhong; Liu, Bin; Bazan, Guillermo C.; Zhou, Jun; Liang, Ziqi
Abstract : Highly bendable n‐type thermoelectric nanocomposites are successfully developed by embedding metallic Ni nanowires within an insulating poly(vinylidene fluoride) (PVDF) matrix in solution. These nanocomposites exhibit an abnormal decoupling of the electrical conductivity and Seebeck coefficient as a function of Ni contents. A maximum power factor of 220 µW m −1 K −2 and ZT of 0.15 can thus be obtained with 80 wt% Ni at 380 K.